ANALISIS KONTRIBUSI EKONOMIS PENJUALAN LANGSUNG LIMBAH PRODUKSI TERHADAP PENDAPATAN DAN BIAYA OPERASIONAL : STUDI KASUS PENGGILINGAN PADI BOKOR - Rahmatulloh, Akhmad Akbar; Niki Puspita Sari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The rice milling sector generates significant residues that are often not optimally managed by Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the economic contribution of direct sales of production waste, specifically husks and bran, to total revenue and the ability to cover operational costs. Unlike the majority of previous literature, which focuses on processing waste into complex derivative products (such as briquettes or functional foods), this study fills a gap by evaluating the efficiency of selling raw waste (without processing) as a low-investment survival strategy. This research employs a quantitative descriptive method with a case study approach at Bokor Rice Mill, analyzing data on production volume, selling prices, and operational cost structure. The analysis results show that waste sales contribute 5.08% to total revenue. The novel contribution of this finding is that waste revenue is able to cover 169.5% of non-raw material operational costs, including electricity, salaries, and machine maintenance expenses. Direct waste sales constitute a vital cross-subsidy mechanism for ensuring the efficiency and financial sustainability of rice milling business units.